Shock response spectrum analysis in running performance - Benjamin, D.; Odof, S.; Abbes, B.; Nolot, J. B.; Erre, D.; Fourchet, F.; Taiar, R. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Running involves repeated impacts between the foot and the surface. Such impacts are characterized by a transient peak in the ground reaction force (impact force), rapid deceleration of the lower extremity (impact shock), and the initiation of a wave of acceleration and deceleration (impact shock wave) that is propagated through the body. The loads produced by repeated impacts have been linked to degenerative joint diseases and athletic overuse injuries including for example stress fractures, shin splints, osteoarthritis and lower back pain. Although the exact mechanisms of impact related injury are relatively unknown and controversial evidence linking impact and injuries is well documented.